ANALISIS HABITUALISASI PROGRAM SMART DAILY PASSWORD SEBAGAI UPAYA MENINGKATKAN KARAKTER SISWA di SEKOLAH DASAR MUHAMMADIYAH SUGIO LAMONGAN - Amalia, Naufa; Sholikhah, Khotimatus; Shoimah, Retno Nuzilatus (Jurnal Murid, 2024)
SD Muhammadiyah Sugio created a program to overcome this problem by implementing the smart daily password program to create efforts to achieve competence and efforts to realize student character in accordance with the Pancasila student profile. The objectives of this study Are 1) To explain and analyze teacher efforts in implementing the smart daily password program to foster student character values 2) To explain and analyze character values contained in the smart daily password language program 3) To explain and analyze challenges and obstacles in implementing the smart daily password language program at SD Muhammadiyah Sugio. The results of the study showed that 1) Cooperation of all parties, including principals, teachers, students and parents to consistently practice good, clear communication with proper grammar through smart daily password activities 2) Character values include discipline, hard work, curiosity, communication, and a love of reading 3) Factors that inhibit the implementation of smart daily passwords include the absence of a guidebook and also the limitations of the media used in smart daily password activities.